99mTc-imidodiphosphonate: a superior radio-pharmaceutical for in vivo positive myocardial infarct imaging. I: Experimental data. Issue 3 (March 1978) - Ell, P J; Langford, R; Pearce, P; Lui, D; Elliott, A T; Woolf, N; Williams, E S
Abstract : 99mTc-Imidodiphosphonate (99mTc-IDP) was investigated as an agent for nuclear medicine imaging of acute myocardial infarctions. For this purpose a suitable animal model was found. After coronary artery ligation reproducible myocardial infarcts were obtained with 80% of surviving animals. Scans of the myocardial infarcts were recorded with a high resolution gamma camera and good quality images were obtained. 99mTc-IDP ratios for normal and infarcted tissue were calculated and compared with similar data available from other 99mTc-labelled phosphates. With an infarct/normal ratio of 21:1, 99mTc-IDP is so far the best radiopharmaceutical for nuclear medicine imaging of necrosed heart muscle. Images of the myocardial infarcts have been recorded as early as 6 hours after infarction.